Implementation of Creative Learning through Pipe Cleaner Crafts Among Children of Indonesian Migrant Workers at Sanggar Bimbingan Kampung Baru, Malaysia - Maslihatul Hasanah; Fitria Nurlita; Ajeng Triwarti (International Journal of Islamic Educational Research, 2026)
This study aims to explore the implementation of creative learning through pipe cleaner crafts among children of Indonesian migrant workers at Sanggar Bimbingan Kampung Baru, Malaysia. The study adopts a qualitative research approach to gain an in-depth understanding of the learning process and participants’ experiences in a non-formal educational setting. Data were collected through observation, interviews, and documentation involving 26 children aged between 4 and 13 years old. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that the implementation of craft-based learning significantly enhances students’ engagement, creativity, and social interaction. The use of pipe cleaner materials encourages active participation and allows children to express their ideas through hands-on activities. In addition, the learning process fosters collaboration among students, contributing to the development of social skills. However, challenges were identified, particularly related to differences in age and levels of understanding among participants.